DAMPAK SSB (SEKOLAH SEPAK BOLA) TERHADAP HASIL BELAJAR SISWA LAKI-LAKI KELAS 5 DAN 6 DI SDN LEDOK 06 SALATIGA - Lusy Andriyani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
The outcomes of the learning process or learning outcomes are one of the things that students need. There are several factors that influence learning outcomes; one of them is external factors; that is the environment. In the area around SD Negeri Ledok 06 Salatiga, the most dominant local community is the SSB (Soccer School). This school attracted the interest to be active in the training of most male students from SD Negeri Ledok 06 Salatiga. Three students have been able to manage their time to keep the focus on their study and join the training in SSB, but there are 2 students who cannot do that. Therefore, supporting factors for the outcomes of learning the are needed, such as parental control for focus divided, as well as control from their teachers can help students to keep the focus on learning at the school.